2020
DOI: 10.1109/access.2020.3033757
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Butterfly Optimization Algorithm for Feature Selection

Abstract: Feature selection represents an essential pre-processing step for a wide range of Machine Learning approaches. Datasets typically contain irrelevant features that may negatively affect the classifier performance. A feature selector can reduce the number of these features and maximise the classifier accuracy. This paper proposes a Dynamic Butterfly Optimization Algorithm (DBOA) as an improved variant to Butterfly Optimization Algorithm (BOA) for feature selection problems. BOA represents one of the most recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 52 publications
0
43
0
1
Order By: Relevance
“…3. like evolutionary algorithms (e.g., genetic algorithms (GA)) [21] and swarm intelligence (SI) techniques (e.g., particle swarm optimization (PSO)), that have been used to solve the FS problem [22], [23] physics based techniques(e.g Gravitational Search Algorithm (GSA)) SI techniques include unlimited algorithms such as Grey Wolf Optimizer (GWO) [24] , Water Cycle Algorithm (WCA) [25] , Whale Optimization Algorithm (WOA) [26], [27], Firefly Algorithm (FA) [28], Salp Swarm Algorithm (SSA) [29] , [30], [31], Emperor Penguin Colony [32] squirrel search algorithm [33], [34], slime mould algorithm (SMA ) [35] , Butterfly Optimization Algorithm [36], [37], Moth Flame Optimization [38], [39] and Marine Predators Algorithm (MPA), which is the most recent and newest SI algorithm [35].…”
Section: Figure 1: Feature Selection Frameworkmentioning
confidence: 99%
“…3. like evolutionary algorithms (e.g., genetic algorithms (GA)) [21] and swarm intelligence (SI) techniques (e.g., particle swarm optimization (PSO)), that have been used to solve the FS problem [22], [23] physics based techniques(e.g Gravitational Search Algorithm (GSA)) SI techniques include unlimited algorithms such as Grey Wolf Optimizer (GWO) [24] , Water Cycle Algorithm (WCA) [25] , Whale Optimization Algorithm (WOA) [26], [27], Firefly Algorithm (FA) [28], Salp Swarm Algorithm (SSA) [29] , [30], [31], Emperor Penguin Colony [32] squirrel search algorithm [33], [34], slime mould algorithm (SMA ) [35] , Butterfly Optimization Algorithm [36], [37], Moth Flame Optimization [38], [39] and Marine Predators Algorithm (MPA), which is the most recent and newest SI algorithm [35].…”
Section: Figure 1: Feature Selection Frameworkmentioning
confidence: 99%
“…Tubishat et al ( 2020 ) suggested dynamic butterfly optimization algorithm (DBOA) as an enhanced version for feature selection issues. Two significant changes have been made in the central BOA: introducing a local search algorithm based on mutation (LSAM) to prevent local optima problems and LSAM usage to increase the variety of BOA solutions.…”
Section: Related Workmentioning
confidence: 99%
“…A streamlined version of the algorithm called a dynamic BO algorithm (DBOA) was also used to perform feature selection problems [38]. The performance of the BOA surpasses that of the PSO.…”
Section: Generalized Bo Algorithmmentioning
confidence: 99%